Allele-specific Silencing of Mutant Myh6 Allele in Mice Suppresses Hypertrophic Cardiomyopathy - Jiang, Jianming (2013)
Dominant mutations in sarcomere proteins such as the myosin heavy chains (MHC) are the leading genetic causes of human hypertrophic cardiomyopathy (HCM) and dilated cardiomyopathy (DCM). Here we demonstrate that expression of the HCM cardiac MHC gene (Myh6) R403Q mutation in mice can be selectively silenced by an RNAi cassette delivered by an adeno-associated virus vector. RNAi-transduced MHC(403/+) mice had neither hypertrophy or myocardial fibrosis, the pathologic manifestations of HCM for at least 6 months. As inhibition of HCM was achieved by only a 25% reduction in the levels of the mutant transcripts, we suggest that the variable clinical phenotype in HCM patients reflects allelic-specific expression and that partial silencing of mutant transcripts may have therapeutic benefit.